2012
DOI: 10.1002/polb.23189
|View full text |Cite
|
Sign up to set email alerts
|

Fast printing of thin, large area, ITO free electrochromics on flexible barrier foil

Abstract: Processing of large area, indium tin oxide (ITO) free electrochromic (EC) devices has been carried out using roll‐to‐roll (R2R) processing. By use of very fine high‐conductive silver grids with a hexagonal structure, it is possible to achieve good transparency of the electrode covered substrates and when used in EC devices switching times are similar to corresponding ITO devices. This is obtained without the uneven switching of larger areas, which is generally observed when using ITO because of its high‐sheet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…[ 17,20 ] A second obstacle in using MCCP in combination with the silver grid electrodes is the blooming effect previously reported and shown in Figure 1 A. [ 10 ] As the areas between the grid lines are non-conductive, the hexagonal grid structures result in an inhomogeneous electrical fi eld between the two electrodes. This requires lateral charge transport for redox switching to occur, and the results is a slow uneven switching, as shown in Figure 1 A.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…[ 17,20 ] A second obstacle in using MCCP in combination with the silver grid electrodes is the blooming effect previously reported and shown in Figure 1 A. [ 10 ] As the areas between the grid lines are non-conductive, the hexagonal grid structures result in an inhomogeneous electrical fi eld between the two electrodes. This requires lateral charge transport for redox switching to occur, and the results is a slow uneven switching, as shown in Figure 1 A.…”
Section: Resultsmentioning
confidence: 97%
“…[ 17,27 ] As the name implies MCCP lends limited absorption to the visible region and we have previously made use of this polymer as a counter polymer in ECDs, due to good solubility and processing properties that allows a wide range of coating applications. [ 10,20 ] These properties qualifi ed MCCP to be one of the best choices as counter polymer for a grid based device. Unfortunately, we found that employing MCCP in a fl exoprinted grid based device produced a slight reddish taint following repeated switches at -1 V to +1 V. By carefully taking the device apart, the discoloring was found to reside on the electrode coated with MCCP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, any even minor damage usually requires the replacement of the entire device. At this point, flexible , foil‐ or textile‐based electrochromic materials represent an appealing, cheaper alternative, because these materials can be integrated far better than glass, offer many more options with regards to interior design and repair and have a by far lower weight. Here, we present our approach, which transfers the principles of electrochromism from glass to flexible textile‐based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Major efforts are currently being devoted to explore and develop new devices and systems for printed electronics applications [1][2][3][4][5][6][7]. The theme of this effort aims at providing novel electronic functionalities on flexible substrates such as plastic foils or papers.…”
Section: Introductionmentioning
confidence: 99%